Enterococcus faecalis: development of a final irrigant to destroy it, analysis of its survival after endodontic treatment and its ability to stimulate pro-inflammatory cytokines after stressed - Zancan, Rafaela Fernandes (2020)
Aim: Ethylene diamine tetracetic acid (EDTA) is used in root canal therapy prior to obturation as a calcium chelator to remove the smear layer. Enhancing the antibacterial properties of EDTA can reduce the irrigation steps and thus reduce treatment time. Furthermore, the use of sodium hypochlorite (NaOCl) can be minimized. There is no clear consensus regarding the ideal irrigation protocol, based on the physical-chemical properties of dentin. As Hydraulic calcium silicate cements (HCSC) are interactive with dentin the effects of previous irrigation might influence sealer adhesion and antimicrobial action. Methodology: Article 1. 17% EDTA without additives and with 1% benzalkonium chloride, 1% N-acetylcysteine or 2% chlorhexidine together with saline control were tested through: antibacterial properties towards monospecies biofilm of Enterococcus faecalis which was inoculated in human dentin either before exposure to irrigating solution or after (confocal laser scanning microscope), ability of removal of smear layer (scanning electron microscope), dentin wettability by the sessile drop method (goniometer), surface tension of solutions (pendent drop test) and viability of fibroblast cells (reducing MTT assay); Article 2. The irreversible damage to dentin produced by NaOCl (2 or 5%), chelating agents (17% EDTA or 17% EDTA + 1% benzalkonium chloride) isolated or in a irrigant protocol and saline were assessed considering: dentin microhardness, morphology and mineral content (scanning electron microscopy and energy dispersive spectroscopy), organic/inorganic matter (Fourier transform infrared spectroscopy), surface roughness and Young`s modulus (atomic force microscope). Characterization of 4 sealers (AH Plus, BioRoot, MTA Fillapex and Total Fill BC Sealer) and their interaction with the dentin interface were analyzed by two techniques (scanning electron microscopy/energy dispersive sectroscopy and confocal laser scanning microscope); Article 3. the effect of 2% NaOCl and 17% EDTA coated dentin on the antimicrobial activity of HCSC ( BioRoot, MTA Fillapex and Total Fill BC Sealer) and AH Plus towards E. faecalis inside dentinal tubules was assed by confocal laser scanning microscope. Results/ Conclusion: Article 1. The additives did not alter the EDTA cytotoxicity or smear layer removal capacity, but increased its antibacterial action. Lower surface tension and better wettability of the irrigants was obtained by the addition benzalkonium chloride or N-acetylcysteine to EDTA. The EDTA benzalkonium chloride solution was the best for prevention of bacteria adherence and dentin wettability; Article 2. Highly concentrated NaOCl followed by EDTA significantly changed inorganic matter dissolution, microhardness and induced a rougher topography on the dentin surface with eroded dentinal tubules. As smear layer was still present on surfaces in NaOCl+chelator groups, the use of EDTA Benzalkonium Chloride (EDTA-BC) or NaOCl final flush was required for further disinfection. Further irrigation with NaOCl resulted in erosion of the dentin around the tubules and smearlayer- free surfaces. Based on CLSM analysis of dentin, the protocols NaOCl/EDTA/NaOCl, or NaOCl/EDTA-BC matched with AH Plus, BioRoot BCS and Total Fill sealers. Microhardness progressively decreased in protocols containing NaOCl 5%, and was recovered after MTA Fillapex or Total Fill application; Article 3. The sealer hydration influenced HCSC antimicrobial activity, as BioRoot BCS a waterbased sealer provided the best antimicrobial activity against E. faecalis. EDTA coated dentin do not harm HCSC antimicrobial action. A smear-free surface enhanced killed bacteria inside dentinal tubules for all sealers.